Abiotic transformation and ecotoxicity change of sulfonamide antibiotics in environmental and water treatment processes: A critical review. (1st September 2021) - Li, Jingchen; Zhao, Lin; Feng, Mingbao; Huang, Ching-Hua; Sun, Peizhe
Highlights: Reaction kinetics of SAs by various oxidants and ROS are summarized. Transformations and toxicity changes of SAs in different processes are reviewed. Treatment technologies are compared from both reaction rate and product toxicity. AOPs combined with biochar or metal oxidants is a future trend for SA treatment. The critical review has strong implications for emerging technological development. Abstract: Sulfonamides (SAs) are among the most widely used antibiotics to treat bacterial infections for humans and animals. They are also used in livestock agriculture to improve growth and feed efficiency in many countries. Recent years, there is a growing concern about the environmental fate and treatment technologies of SAs, in order to eliminate their potential impact on the ecosystem and human health. Additionally, SAs are frequently used as model compounds to evaluate the performance of newly developed advanced water treatment processes. Hence, understanding the chemical reaction features of SAs can provide valuable information for further technological development. In this review, the reaction kinetics, abiotic transformations and corresponding ecotoxicity changes of SAs in natural environments and water treatment processes were comprehensively analyzed to draw critical suggestion and new insights. The OH-based AOP is proposed as an effective method for the elimination of SAs toxicity, although it is susceptible to water constituent due to low selectivity. The application of biochar or metal-based oxidants in AOPs is becoming a future trend for SA treatment. Overall, this review would provide useful information for the development of advanced water treatment technologies and the control of ecological risks related to SAs. Graphical abstract: Image, graphical abstract